Unpacking account-based marketing: Conceptualization, key activities, and performance outcomes - Severini, Simone; Terho, Harri; Mero, Joel; Cardinali, Silvio (Elsevier, 2026)
Account-Based Marketing (ABM) is gaining momentum in business-to-business (B2B) markets, but academic research on the topic remains embryonic. Most existing knowledge on ABM originates from practitioner sources, which often lack theoretical grounding and fail to clearly distinguish ABM from other marketing approaches. Consequently, ambiguity persists regarding the defining characteristics of ABM, the specific activities it entails across the sales process, and the outcomes it is expected to deliver. To address these gaps, this study aims to conceptualize ABM processes by leveraging existing literature and a qualitative Theories-in-Use (TIU) approach across diverse B2B industries. The empirical findings offer three novel contributions: (1) a clear conceptualization of the ABM process and its core activities, (2) structured insights into how these activities vary across different stages of the sales cycle, and (3) ABM framework that explains how ABM can create value for KAM sales process and improve organizational performance. These insights also provide actionable guidance for practitioners seeking to develop and improve ABM within their organizations.